An approach for validated RP-HPLC method for the analysis of paclitaxel in rat plasma - Nandhakumar Sathyamoorthy, Vijayalakshmi Rajendran, Naveena V.S.H, Magharla Dasaratha Dhanaraju (Journal of Applied Pharmaceutical Science, 2014)
This report describes analysis of paclitaxel, which is an antineoplastic drug used in the treatment of kaposi's sarcoma and cancer of the lung by isocratic high performace liquid chromatography with UV detection in pure form and rat plasma. The analysis was carried out using phenomenex C18 (250 x 4.6 mm, 5 µm particle size) column with a mobile phase consisting of acetonitrile and phosphate buffer (pH 5) in the ratio of 80:20%, v/v. Paclitaxel was eluted at the retention time of 5.3 min when operated at the flow rate of 1 ml/min and monitored by UV at 227 nm. Paclitaxel was extracted from rat plasma by simple LLE method using non- toxic ethyl acetate as extraction solvent. The linearity was accessed in the concentration range of 100-600 µg/mL with correlation coefficient of 0.9999 and percentage recovery of 99.86. The liquid chromatography method was extensively validated for linearity, accuracy, precision, LOD, LOQ and robustness. All these analytical validation parameters were observed to be satisfactory, which indicates the usefulness of method for determination of paclitaxel in pure form and rat plasma. No interfering peaks were observed during the analysis.
Keywords: Paclitaxl, validation, RP-HPLC,acetonitrile, Buffer (pH 5).